Unravelling the Adiponectin Hallmark and Exploring the Therapeutic Potential of Its Receptor Agonists in Cancer Metabolic Reprogramming - Sanober Kafeel; Giuseppina Palmiero; Alessia Salzillo; Angela Ragone; Silvio Naviglio; Luigi Sapio (Biomolecules)
As the most abundant fat-derived hormone, adiponectin plays an essential role in regulating energy homeostasis. Current evidence proposes the serum levels of adiponectin as a risk factor and a diagnostic/prognostic biomarker in cancer. Moreover, distinctive antineoplastic features have also been reported as a result of adiponectin supplementation in preclinical models. Mapping of the cancer-associated metabolic changes has elucidated a highly adaptable and interconnected system that allows malignant cells to sustain their growth and survival. Along with the pyruvate into acetyl-CoA conversion, downregulation of both lactate dehydrogenase and glycolysis-related genes depicts the main adiponectin-induced perturbations affecting glucose metabolism in cancer. Meanwhile, a multi-level approach involving lipid trafficking, catabolism, and de novo synthesis has been attributed to adiponectin in malignancies. The adiponectin receptor agonist AdipoRon has recently been recognized as a promising antineoplastic compound. Remarkably, AdipoRon-mediated changes in cancer metabolism occur together with its antiproliferative potential. This review aimed at recapitulating the modulatory effects of adiponectin, as well as those of its synthetic receptor agonists, in driving metabolic alterations in cancerous cells. A critical discussion is also conducted to deduce whether the adiponectin axis could serve as a putative target to address the metabolic reprogramming in cancer progression.